2021
DOI: 10.1136/bmjophth-2021-000754
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of keratoconus in persons with Down syndrome: a review

Abstract: PurposeKeratoconus is a vision-threatening condition, and there is a need for knowledge about the occurrence in subgroups of the population. The progression of the disease can be effectively stopped, and vision may be restored, if keratoconus is diagnosed at an early stage. The purpose of this review was to evaluate the literature of the prevalence of keratoconus in persons with Down syndrome.MethodsWe conducted a literature review of keratoconus prevalence in persons with Down syndrome. A thorough search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Keratoconus does not typically manifest until the second decade of life, and therefore, the prevalence of keratoconus in these studied populations would be expected to be very low at most. In contrast, a review of keratoconus prevalence rates in Down syndrome patients found higher rates (>10%) of keratoconus reported in studies that utilized corneal topography as the standard diagnostic tool [ 54 ]. Furthermore, a more recent study of pediatric patients with Down syndrome detected keratoconus suspicion or definite keratoconus using Schiempflug tomography in at least one eye of 32% of patients [ 55 ], again suggesting that with more sensitive diagnostic technologies, keratoconus is more likely to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Keratoconus does not typically manifest until the second decade of life, and therefore, the prevalence of keratoconus in these studied populations would be expected to be very low at most. In contrast, a review of keratoconus prevalence rates in Down syndrome patients found higher rates (>10%) of keratoconus reported in studies that utilized corneal topography as the standard diagnostic tool [ 54 ]. Furthermore, a more recent study of pediatric patients with Down syndrome detected keratoconus suspicion or definite keratoconus using Schiempflug tomography in at least one eye of 32% of patients [ 55 ], again suggesting that with more sensitive diagnostic technologies, keratoconus is more likely to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that total corneal refractive powers are significantly higher in females, which leads to steeper corneas and a higher probability of having keratoconus [ 24 ]. On the contrary, Kristianslund et al [ 25 ] found that more than six studies have reported a predominance of keratoconus in males. Otherwise, in the same study, two studies did not find differences or associations in the diagnosis of keratoconus as in our study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Kristianslund et al [ 25 ] found that more than six studies have reported a predominance of keratoconus in males. Otherwise, in the same study, two studies did not find differences or associations in the diagnosis of keratoconus as in our study [ 25 ]. Considering the number of studies and the discrepancies between them, conducting a systematic review with a meta-analysis that summarizes and statistically analyzes this association between keratoconus and DS is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…There are various ocular manifestations associated with DS, such as strabismus, amblyopia, nystagmus, accommodation deficits, nasolacrimal duct obstruction, keratoconus, optic nerve pathology, neoplastic disease and retinal pathology [ 113 ]. A review highlighted that keratoconus, a corneal dystrophy leading to progressive visual impairment, was reported by 0–71% of individuals with DS [ 113 ]. It is important to note that the cornea and brain have the highest concentration of keratan sulphate proteoglycan in the human body [ 114 ].…”
Section: Gene Expression Changes Affecting Ocular Developmentmentioning
confidence: 99%